YouTube dan Online Sharing - Pramana, M. Agung; Triantoro, Dony Arung (Universitas 17 Agustus 1945 Surabaya, 2025)
This article examines the response of Indonesian netizens to the presence of YouTube media with a focus on the YouTube channel @Mager_Nonton, a channel that discusses the storyline of films, especially foreign films. Previous research only focused on analyzing YouTube content and the messages it wanted to convey. This research comes as an update that netizens place an important role in video content, such as interacting in the comments column and so on. This article attempts to answer the main question, namely how do netizens interpret the content from the YouTube channel @Mager_Nonton and what are the conversations between netizens? Meanwhile, the follow-up question is, how is the presence of YouTube media in Indonesia? To answer this question, the author used the netnography method on the YouTube channel @Mager_Nonton, then the author read subscribers, likes and comments from netizens regarding the content displayed, then analyzed it with relevant previous literature. The results of the research show that netizens respond to the YouTube channel @Mager_Nonton as a place to discuss, share the content of the film storylines they see in the comments column, and also as a place to add insight and new knowledge related to films among netizens who comment, such as sharing information regarding the cast movies in the real world.